2013
DOI: 10.1007/s10903-013-9867-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Refugee Children Entering DeKalb County, Georgia

Abstract: This study determines the nutritional status among refugee children entering one of the largest resettlement counties in the United States and identifies differences between incoming populations. Medical records of all newly arriving pediatric refugees (0-18 years) entering DeKalb County, Georgia between October 2010 and July 2011 were reviewed. Refugee children were grouped as African, Bhutanese, or Burmese (resettling from either Thailand or Malaysia) for comparative analysis. Approximately one in five refug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
1
13
0
5
Order By: Relevance
“…Oral health status of refugee children Three studies included a clinical oral health examination undertaken by an oral healthcare professional (Vered et al, 2008;Gibbs et al, 2015;Nicol et al, 2015). The remaining four quantitative studies reported only retrospective clinical data recorded as part of a refugee general health assessment (Melvin, 2006;Johnston et al, 2012;Mutch et al, 2012;Shah et al, 2014). The origin of these audit data varied but in only one study was an oral healthcare professional involved in the dental screening (Melvin, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral health status of refugee children Three studies included a clinical oral health examination undertaken by an oral healthcare professional (Vered et al, 2008;Gibbs et al, 2015;Nicol et al, 2015). The remaining four quantitative studies reported only retrospective clinical data recorded as part of a refugee general health assessment (Melvin, 2006;Johnston et al, 2012;Mutch et al, 2012;Shah et al, 2014). The origin of these audit data varied but in only one study was an oral healthcare professional involved in the dental screening (Melvin, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Disappointingly, but consistent with much of the wider dental literature, there was a lack of consistency and quality of both the screening protocols and the instruments used to diagnose dental caries. Most of the studies use data from either retrospective review of medical records (Johnston et al , ; Mutch et al , ; Shah et al , ) or ‘dental screenings’ that are not comprehensive; hence, caries experience may be under reported (Melvin, ; Nicol et al , ). International standards for epidemiological oral health studies encourage consistency through the use of the International Caries Detection and Assessment System (ICDAS II) (Ismail et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The median time interval from OME to DME in our study was 5.5 months (IQR 4.3–6.5 months); therefore, similar prevalence estimates may be found when comparing malnutrition at the OME to the DME. One study evaluated the prevalence of wasting and stunting among refugee children under 5 years old overall and by country of origin at their DME in DeKalb County, Georgia (GA) from 2010–2011 [ 30 ]. This GA study found that children under 5 years old had a 12% prevalence of wasting at the DME, which was comparable to the 14.3% observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these findings highlight the importance of presenting results by country of origin 11,12 to tailor surveillance and interventions based on the needs of refugee populations.…”
Section: Figurementioning
confidence: 99%
“…14 -16 Refugee children arrive in the United States with variable nutritional status based on their preresettlement experiences. 9,12,17,18 Although several studies have reported an increase in the prevalence of obesity and obesity-related diseases among adult refugees and an increase in their BMI trajectories after US resettlement, the data among child refugees is limited. 19,20 Two small studies demonstrated a trend toward increasing obesity prevalence among refugee children.…”
Section: What This Study Addsmentioning
confidence: 99%